Pengaruh Harga Pokok Penjualan, Aset Tetap Dan Hutang Jangka Panjang Terhadap Laba Bersih Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Indeks Saham Syariah Indonesia (ISSI) Tahun 2017-2022 - Muhammad Rayyan; Fathurrahman Fathurrahman; Sri Rahma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to determine the effect of cost of goods sold, fixed assets and long-term debt on the net profit of consumer goods industry sector companies listed on the Indonesian sharia stock index (ISSI) 2017-2022. This research uses independent variables, namely cost of goods sold, fixed assets and long-term debt. The dependent variable is net profit. The data used in this research is secondary data, namely in the form of financial reports of companies in the consumer goods industry sector listed on the Indonesian sharia stock index (ISSI) 2017-2022. This research is descriptive with a quantitative approach. Statistical methods use multiple linear regression analysis, t test, f test, and coefficient of determination analysis. The results of this research show that cost of goods sold has a significant effect on net profit, fixed assets have a significant effect on net profit, and long-term debt partially has no significant effect on net profit. Then the cost of goods sold, fixed assets and long-term debt simultaneously influence net profit. By using the F test, it is found that the independent variable has a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all independent variables are 0.559 or 55.9%, meaning that net profit can be explained by the cost of goods sold, fixed assets and long-term debt of 55.9%. while the remaining 44.1% can be explained by other factors outside this research.